Strength and conditioning program for preparing 2020 season by 2019 national and oceania men's pole vault champion - Burgess, P. G.; Hori, N. (Journal of Australian Strength and Conditioning, 2020)
Pole vault is an event within the sport of athletics. This article details the 26-week strength and conditioning program completed by Angus Armstrong (2019 Australian National Champion, 2019 Oceania Champion) as preparation towards his 2020 Australian domestic season. During August and September, improving the physical capacity of the athlete was prioritised. During this period, four weight training sessions, two running sessions and one gymnastics session were completed each week. From October, two pole vault sessions were added, and weight training sessions were reduced to twice per week. As each block was increased in intensity while volume was decreased, running continued to be programmed twice per week during October, then was reduced to once per week through November, before being taken out of the program from December. In weight training, throughout the year, priority was given to the exercises with large muscle mass, multiple joints, ground based, and large range of motion. When a strategic teaching process was needed for certain exercises (e.g. power clean and power snatch), or rate of force development at a specific range was emphasised (e.g. ¼ back squat and ¼ Bulgarian squat), exercises were performed with partial range. In November and December, chin up, ¼ back squat, and ¼ Bulgarian squat were performed eccentrically in order to 1) build psychological confidence, 2) recruit higher threshold motor units, and 3) condition to large eccentric force encountered during pole vaulting. As the season commenced, resistance priming was introduced on the day preceding competitions. At the first competition from a full run up of the 2020 domestic season in February, the athlete improved his personal best from 5.52m to 5.63m.